Pengaruh Penggunaan Gaya Bahasa Gaul Oleh Kedua Orangtua Terhadap Perkembangan Kosa Kata Dan Cara Berbahasa Pada Anak Usia Dini - Hardi Yasa Putra, Pandu; Azzam Nasution, Ahmad; Jonathan, Kevin; Heru Mu'afa, Akhdan; Fahmi AH, Maulana; Puspa A, Dewi (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This study aims to analyze the influence of parents' use of slang on the development of children's vocabulary at an early age. Children's language development is an important aspect of their cognitive and social growth, and environmental factors, including communication with parents, play a key role in this. With the increasing use of slang in daily interactions, this research tests whether the language used by parents, especially those containing slang elements, can influence children's ability to develop a broader and more meaningful vocabulary. This research uses a qualitative approach with observation and interview methods with parents and children aged 3-5 years. The results of the research show that the use of slang by parents has a significant influence on the development of children's vocabulary, both in terms of the variety of words used and understanding the meaning of these words. However, this influence depends on the context of slang use and the interactions that take place between parents and children. These findings provide important insights for educators and parents considering the impact of language used in everyday communication on children's language development.